Incorrect Identification in the Marketing of Serrasalmid Fishes: A Threat to Native Species and Productivity in the Aquaculture Industry - Martins, Diego G. [UNESP]; Prado, Fernanda D.; Utsunomia, Ricardo [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Goes, Caio Augusto Gomes [UNESP]; Foresti, Fausto [UNESP]; Rodrigues, Carlos Egberto; Porto-Foresti, Fabio [UNESP] (MDPI, 2025)
Interspecific hybridization can offer advantages in fish aquaculture by enhancing traits like growth rate and disease resistance. However, improper management can result in heterogeneous breeding stocks, which pose risks if hybrids interbreed with native populations. This can lead to loss of genetic diversity and alterations in population structure. This study aimed to evaluate the prevalence of hybridization within the Brazilian aquaculture industry, focusing on the economically significant Serrasalmid species, such as Piaractus mesopotamicus (pacu), Piaractus brachypomus (pirapitinga), Colossoma macropomum (tambaqui), and their hybrids. Using molecular markers (TROP and APOC SNP markers), 312 individuals from the Companhia de Entrepostos e Armazéns Gerais de São Paulo (CEAGESP), the largest warehouse in Latin America, were assessed. The results revealed that 80% of the samples were misidentified, with a substantial proportion of hybrids (72.12%). Among these hybrids, 71.6% were classified as F1 hybrids, while 28.4% were post-F1 hybrids. These findings highlight the need for improved genetic monitoring and management practices in Brazil’s fish production industry, emphasizing the importance of sustainable practices to ensure the long-term viability of aquaculture while preserving native genetic resources.